Neonatal adrenal findings: significance and diagnostic approach. Description of two cases. Issue 4 (21st February 2018) - Angelis, Dimitrios; Mudduluru, Manjula; Joseph, Sonia; Ching, Christopher; Hughes, Amanda; Bennett, Robert
Key Clinical Message: Abnormal adrenal findings such as hemorrhage or calcifications in the neonate can stem from a variety of etiologies. Clinical presentation can vary significantly based on the degree of hemorrhage or the associated condition. Thorough work‐up is important to rule out critical underlying conditions as well as adrenal insufficiency. Abstract : Abnormal adrenal findings such as hemorrhage or calcifications in the neonate can stem from a variety of etiologies. Clinical presentation can vary significantly based on the degree of hemorrhage or the associated condition. Thorough work‐up is important to rule out critical underlying conditions as well as adrenal insufficiency.